Advanced IT tools IFIP World Conference on IT Tools, 2-6 September 1996, Canberra, Australia - Terashima, Nobuyoshi; Altman, Edward (Chapman & Hall, 1996)
This book provides a state-of-the-art review of information technology tools for multimedia and its applications. It explores specifically the integration of multimedia applications and the information superhighway. The book is divided into three main parts. Part one discusses innovative applications in the public sector. Multimedia and intelligent systems will have a significant influence in many aspects of the public sector in the future. Part two is entitled Innovative Applications on the Horizon, and is concerned with turning current technological opportunities into real benefits in the future. Part three, Intelligent Systems, deals with systems used for application development, platforms for these systems and intelligent applications.